Liberty - Berlin, Isaiah; Hardy, Henry; Harris, Ian (Oxford : Oxford University Press, 2007)
Five essays on liberty / Isaiah Berlin ## Other writings on liberty / Isaiah Berlin ## Autobiographical appendices / Isaiah Berlin ## Berlin and his critics / Ian Harris ## Concordance to Four essays on liberty
With an essay on Berlin and his critics by Ian harris
Onderzoek KASK Professioneel (OFVP)
boek
Keywords: Berlin, Isaiah